Automating a Modified Personal Software Process - Md. Nasir, Mohd Hairul Nizam; M. Yusof, Azwina (Malaysian Journal of Computer Science, 2005)
Personal Software Process (PSP) is a defined software development framework that includes defined operations, measurement and analysis techniques to assist software engineers to understand and build their own skills in order to improve their own personal performance. Even though several published studies have suggested that adopting PSP results in improved size and time estimation, and improved numbers of defects found in the compiled and test phases of software development, nevertheless not every software engineer adopts PSP in the process of software development .This paper attempts to clarify the issues that influence the adoption of PSP and explain how an automated tool can address these problems. The PSP adoption issue has been identified to be due to four reasons; 1) overhead in data collection and analysis, 2) excessive use of forms combined with a lack of a fully automated tool, 3) freezing of process definition, and 4) privacy issue. This paper describes an automated web based application tool to support the adoption of PSP in software development, called PSP.NET. This fully-automated tool can simplify both data collection and analysis to make this discipline more manageable and organized, with added features to make it more flexible, such as anti freezing of process definition, privacy support and collaborative sharing of defect information.